1999
DOI: 10.1073/pnas.96.12.6722
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-coated vesicles bearing GAIP possess GTPase-activating protein activity in vitro

Abstract: G␣-interacting protein (GAIP) is a member of the RGS (regulators of G protein signaling) family, which serve as GAPs (GTPase-activating proteins) for G␣ subunits. Previously, we demonstrated that GAIP is localized on clathrin-coated vesicles (CCVs). Here, we tested whether GAIPenriched vesicles could accelerate the GTPase activity of G␣ i proteins. A rat liver fraction containing vesicular carriers (CV2) was enriched (4.5؋) for GAIP by quantitative immunoblotting, and GAIP was detected on some of the vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…Indeed, RGS9 -2 accelerates the off-kinetics of D 2 R-induced GIRK currents (Rahman et al, 2003), whereas GAIP was here found to participate in the regulation of adenylate cyclase and phospholipase A2 signaling cascades as well as in vesicular trafficking in accordance with previous studies (Lou et al, 2002;Wylie et al, 2003). In agreement with this latter observation, GAIP and GIPC were closely associated with clathrin as assessed by electron microscopy (De Vries et al, 1998a;Fischer et al, 1999). Additionally, we showed that D 2 R, GIPC and GAIP colocalized within microdomains of the PM, probably clathrin-coated pits, where GFPGAIP codistributed upon D 2 R activation.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, RGS9 -2 accelerates the off-kinetics of D 2 R-induced GIRK currents (Rahman et al, 2003), whereas GAIP was here found to participate in the regulation of adenylate cyclase and phospholipase A2 signaling cascades as well as in vesicular trafficking in accordance with previous studies (Lou et al, 2002;Wylie et al, 2003). In agreement with this latter observation, GAIP and GIPC were closely associated with clathrin as assessed by electron microscopy (De Vries et al, 1998a;Fischer et al, 1999). Additionally, we showed that D 2 R, GIPC and GAIP colocalized within microdomains of the PM, probably clathrin-coated pits, where GFPGAIP codistributed upon D 2 R activation.…”
Section: Discussionsupporting
confidence: 80%
“…GIPN was cloned into pcDNA3 (Invitrogen) with an N-terminal FLAG-tag and prepared by using the TnT reticulocyte lysate kit (Promega) in the presence of [ 35 S]methionine. Five micrograms of His6-GAIP (17) and AGS3 (residues 424-650; ref. 18) were immobilized on Ni 2ϩ -agarose beads (Qiagen, Valencia, CA) and incubated with 35 S-labeled GIPN for 1 h at 4°C in 300 l of buffer A (20 mM Hepes, pH 7.4͞150 mM NaCl͞0.5 mM EDTA͞0.1% Triton X-100͞0.1 g/ l BSA) with gentle rocking.…”
Section: Isolation Of Mammalian Gipn Cdnasmentioning
confidence: 99%
“…13 and 14). We localized one member of the RGS family, RGS-GAIP (G ␣ interacting protein), by immunocytochemistry and found it to be associated with clathrincoated pits and vesicles (15,16) and further demonstrated that CCVs isolated from rat liver possess GAP activity (16).…”
mentioning
confidence: 99%
“…13 and 14). We localized one member of the RGS family, RGS-GAIP (G ␣ interacting protein), by immunocytochemistry and found it to be associated with clathrincoated pits and vesicles (15,16) and further demonstrated that CCVs isolated from rat liver possess GAP activity (16).Clathrin-coated vesicles (CCVs) are known to play a role in G-protein coupled receptor-(2) and receptor-mediated endocytosis at the plasma membrane and in sorting of lysosomal enzymes in the trans-Golgi network (TGN) (17)(18)(19). Formation of CCVs is known to be tightly regulated by phosphorylation and dephosphorylation of adapters and coat proteins (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
See 1 more Smart Citation